Design and development of a multi-purpose modular solar cell facade - Rungruengsorakarn, Charan; Hirunlabh, Jongjit; Suphahitanukool, Chaiporn; Sathibunanan, Sumate; Khedari, Joseph (Frontiers in Engineering Innovation Research, 2024)
This research focuses on the development of building facades by designing and installing multifunctional modular solar panels to facilitate assembly and installation. The aim is to modernize the building facade while evaluating the efficiency of electricity production from the solar panels and the effectiveness of heat reduction in the building. The building facade consists of an outer wall made of composite panels with 150-watt solar panels installed. The side and rear walls are made of composite panels and insulated with standard foam insulation for the module, measuring 1.2 meters wide, 2.4 meters long, and 0.3 meters high. The modules are installed facing southwest. A comparative design was made for opening and closing the module openings, and measurements were taken over a period of 120 days. The heat flux transmitted through solar radiation was measured, along with the temperature and electricity production from the solar panels. The results of the efficiency tests for electricity production from solar energy in the perforated facade showed an average of 0.3017 kilowatt-hours per day, which is higher than the average of 0.27792 kilowatt-hours per day for the non-perforated façade. The electricity production varies with temperature; on hotter days, the heat flux transmitted through solar radiation is higher, resulting in increased electricity production from solar energy. Additionally, the temperature of the ventilated modules is significantly lower than that of the non-ventilated modules, with a maximum temperature difference of 2 degrees Celsius between the two modules. Therefore, the design of the building facade, combined with the installation of solar panels and the ventilation openings of this multifunctional module, represents a new approach to the sustainable exterior design of residential buildings, contributing to clean energy production and reducing heat in building walls.